Aligning public financial management system and free healthcare policies: Lessons from a free maternal and child healthcare programme in Nigeria - Daniel Chukwuemeka Ogbuabor; Obinna Emmanuel Onwujekwe (Health Economics Review, 2019)
Background: Relatively little is known about how public financial management (PFM) systems and health financing policies align in low- and middle-income countries. This study assessed the alignment of PFM systems with health financing functions in the free maternal and child healthcare programme (FMCHP) of Enugu State, Nigeria. Methods: Data were collected through quantitative and qualitative document review, and semi-structured, indepth interview with 16 purposively selected policymakers involved in FMCHP. Data collection and analysis were by guided a framework for assessing alignment of PFM systems and health financing policies. Revenue and expenditure trend analyses were done using descriptive statistics and analysis of variance (ANOVA). Level of significance was set at ? < 0.05. Qualitative data were analysed using a framework approach. Results: The results showed that no more than 50% of FMCHP fund were collected despite that the promised fund remained unchanged since inception. Revenue generation significantly varied between 2010 and 2016 (? < 0.05). Level of pooling was limited by non-compliance with contribution rules, recurrent unauthorised expenditure and absence of expenditure caps. The unauthorised expenditure significantly varied between 2010 and 2016 (? < 0.05). Misalignment of budget monitoring and purchasing revealed absence of auditing and delays in provider payment. Refunds to providers significantly varied between 2010 and 2016 (? < 0.05) due to weak Steering Committee, weak vetting team, paper-based claims management and institutional conflicts between Ministry of Health and districtlevel officials. Conclusions: This study identified important lessons to align PFM systems and FMCHP. A realistic and evidenceinformed budget and enforcement of contribution rules are critical to adequate and sustainable revenue generation. Clarity of roles for various FMCHP committees and use of clear resource allocation strategy would strengthen pooling and fund management. Enforcement of provider payment standards, regular auditing, and a stronger role for the parliament in budgetary processes are warranted.
Keywords: 330; Public financial management; Free healthcare; Policy implementation; Nigeria